2015
DOI: 10.3109/10641963.2015.1026041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a selective aldosterone blocker and thiazide-type diuretic on blood pressure and organ damage in hypertensive patients

Abstract: The aim of the present study was to compare the effects of the aldosterone blocker eplerenone and thiazide-like diuretic indapamide on blood pressure (BP) and target organs with reference to salt intake in hypertensive outpatients. Twenty hypertensive patients (nine women and 11 men, mean age 71 ± 13 years) with inadequate BP control despite taking calcium channel blockers (CCBs) and angiotensin II receptor blockers (ARBs) were administered eplerenone (50 mg/day) or indapamide (1 mg/day) for 3 months each in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…There have been only two studies that examined the effect of eplerenone on home BP (but not in RH): one was a retrospective study of 83 hypertensive patients with 8 weeks of eplerenone treatment wherein home SBP/DBP decreased by −7.1±10.1/−2.6±5.0 mm Hg ( P <.0001), but this was a single‐arm study. The other study compared the efficacy of add‐on eplerenone and add‐on indapamide on home BP and showed that eplerenone (−10±10/−4±6 mm Hg) and indapamide (−15±10/−7±6 mm Hg) were equally effective in lowering home BP . On the other hand, low‐dose spironolactone was shown to be effective in lowering home BP .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been only two studies that examined the effect of eplerenone on home BP (but not in RH): one was a retrospective study of 83 hypertensive patients with 8 weeks of eplerenone treatment wherein home SBP/DBP decreased by −7.1±10.1/−2.6±5.0 mm Hg ( P <.0001), but this was a single‐arm study. The other study compared the efficacy of add‐on eplerenone and add‐on indapamide on home BP and showed that eplerenone (−10±10/−4±6 mm Hg) and indapamide (−15±10/−7±6 mm Hg) were equally effective in lowering home BP . On the other hand, low‐dose spironolactone was shown to be effective in lowering home BP .…”
Section: Discussionmentioning
confidence: 99%
“…The other study compared the efficacy of add-on eplerenone and add-on indapamide on home BP and showed that eplerenone (À10AE10/À4AE6 mm Hg) and indapamide (À15AE10/À7AE6 mm Hg) were equally effective in lowering home BP. 21 On the other hand, low-dose spironolactone was shown to be effective in lowering home BP. 22 Because ambulatory BP assesses only 1-day BP, the additional confirmation of BP-lowering effects by home BP monitoring could provide a more robust assessment of BP lowering.…”
Section: Eplerenone and Ambulatory And Home Bpmentioning
confidence: 99%
“…MRAs even outperform other diuretics in improving arterial stiffness [72]. Their beneficial effects extend to endothelium-dependent flow-mediated vasodilatation [73], likely due to the role of MR in the modulation of endothelial stiffness and function [51,74,75•], and to highly specialised vascular beds such as coronary circulation [76,77].…”
Section: Would Targeting Tissue Na + Improve Resistance?mentioning
confidence: 99%
“…Previous clinical studies reported that eplerenone significantly reduced urinary albumin compared with amlodipine or enalapril, 19 but only a few studies have investigated its effect on albuminuria by comparison with thiazide diuretics. 29 The lack of clinical data on eplerenone may have been because of restriction of its administration for patients with diabetic nephropathy with overt proteinuria and patients with chronic kidney disease with moderate or severe renal dysfunction.…”
Section: Ras Inhibitors (Angiotensin-converting Enzyme Inhibitor or Arb)mentioning
confidence: 99%